Anaysis of the Roe and Functions of the Finance Section of BAPPEDA in the Sustainabiity of Medan City Panning and Deveopment - Ridho Fachrozie; Wahyu Syarvina (Penerbit Jurnal Indonesia, 2022)
Bappeda is an agency engaged in panning and deveopment, which reguates and manages the course of panning and deveopment in the city of Medan. Within Bappeda there is a corporate organizationa structure, among which there is a structure for the finance department, which carries out some of the tasks of financia management. This study aims to determine specificay the roe and function of the Bappeda section in panning and deveoping the city of Medan. The approach taken in this research is to use a quaitative approach using the iterature method. The research data was obtained from the company directy and coected writings from severa artices, severa books, and a forms of sources reated to the object of research. The resuts of this study indicate the importance of the roe and function of the finance department in Medan city deveopment panning.